2009
DOI: 10.1680/geot.2008.t.003
|View full text |Cite
|
Sign up to set email alerts
|

Particle breakage during cyclic triaxial loading of a carbonate sand

Abstract: Dynamic loading of embankment, foundation and pavement structures results in particle breakage of the constituent granular materials, when the stresses imposed on their particles exceed their strength. This paper presents the results of a number of drained cyclic triaxial tests on loose, uniformly graded samples of Dogs bay carbonate sand. It is observed that particle breakage is dependent on stress level, cyclic stress ratio, and creep and is directly related to volumetric strain. Drained cycling increases vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 124 publications
(54 citation statements)
references
References 21 publications
3
50
0
1
Order By: Relevance
“…This method for quantifying breakage using particle size distributions is commonly used in the field of soil mechanics (e.g., Coop et al, 2004;Donohue et al, 2009). Particle size distributions are often presented as shown in Fig.…”
Section: Relative Breakagementioning
confidence: 99%
See 1 more Smart Citation
“…This method for quantifying breakage using particle size distributions is commonly used in the field of soil mechanics (e.g., Coop et al, 2004;Donohue et al, 2009). Particle size distributions are often presented as shown in Fig.…”
Section: Relative Breakagementioning
confidence: 99%
“…Hardin used 74 lm although other researchers have used different values, e.g., Coop et al (2004) and Donohue et al (2009) both used 63 lm. For this work, 20 lm was chosen as measured changes in the particle size distributions of infant formulae below this threshold were negligible, even where attrition was high.…”
Section: Relative Breakagementioning
confidence: 99%
“…In recognition of its importance in many geotechnical engineering applications, such as cone penetrometer testing, displacement pile driving, and high earth or rock-fill dams, where the effective stresses acting on soils can be high enough to fracture grains of the strongest soil minerals [1][2][3], many authors have investigated the effects of grain crushing on the stress-strain, deformation, yielding, hardening and softening, and critical state behavior of sands (e.g. [4][5][6][7][8][9][10][11][12]). It is found that grain crushing is most affected by mineralogy (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…where P s is the survival probability of a particle with size d, s = F/d 2 (F is the force measured in the platen compression test) is the induced tensile stress, s 0 is the characteristic tensile stress at which 1/e or 37% of the tested particles survive, and m is the Weibull modulus. On this basis, a wealth of theoretical and numerical modeling work has been carried out to estimate the effects of particle crushing on sand behavior under a variety of stress paths [8,12,[19][20][21][22]. In particular, the discrete element method (DEM) has achieved notable success in unraveling the particle-scale mechanisms (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation